Environmental, Social, and Governance Investment in Emerging Markets: A Case Study of Firms in ASEAN - Korwatanasakul, Upalat; Majoe, Adam (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2021)
This study examines the current situation of environmental, social, and governance (ESG) investment in Association of Southeast Asian Nations (ASEAN) countries. Based on a purposive sampling, our sample includes 143 leading firms from 10 ASEAN countries. By intensively reviewing firms’ multiyear annual and sustainability reports, we utilize content analysis to identify the characteristics of ESG firms (firms considering ESG factors in their investment decision-making process). Our result shows that ESG firms, on average, have higher profitability. Moreover, ESG investment helps lower costs and boost revenue and profits. However, ESG investment has only been implicitly and unsystematically implemented in ASEAN firms.